Análisis funcional de acuaporinas subtipo PIP y mutantes para investigar la actividad del canal como transportador de agua - Yaneff, Agustín (2015)
The plant aquaporin PIP subfamily represents one of the main gateways for water exchange at\nthe level of the plasma membrane. Among them, a fraction of this subfamily -known as PIP1-\ndoes not reach the plasma membrane unless they are co-expressed with a PIP2 aquaporin.\nAlthough ubiquitous and abundantly expressed, the role and properties of PIP1 aquaporins\nhave therefore remained masked. Here we unravel how FaPIP1;1 -a fruit specific PIP1\naquaporin from Fragaria x ananassa- contributes to modulate membrane water permeability (Pf)\nusing a mathematical model approach applied to experimentally obtained Pf from different coexpression ratios of FaPIP1;1 and FaPIP2;1 or a FaPIP2;1 mutant. For the first time we dissect the individual contribution of each PIP when co-expressed in Xenopus oocytes, showing that i) PIP1 has also high water transport capacity when co-expressed with PIP2; ii) PIP2 water permeability is enhanced when it physically interacts with PIP1; iii) PIP1-PIP2 seem to form heterotetramers with a random stoichiometry arrangement. Also, we characterized FaPIP2;1 and FaPIP1;1 pH gating sensitivity and how the phosphorylation status of a specific Serine could influence in this response. A crosstalk between different regulatory mechanisms that would rule the Pf of a membrane that express PIPs is proposed.